Overlooked effect of ordinary inorganic ions on polyaluminum-chloride coagulation treatment. (15th May 2023) - Chen, Yize; Matsui, Yoshihiko; Sato, Tsutomu; Shirasaki, Nobutaka; Matsushita, Taku
Highlights: Hydrolysis explains the dependence of coagulation on type of PACl and raw water. Hydrolysis and coagulation depend on type of PACl and the anions in the raw water. Effects of sulfate, bicarbonate, and NOM in raw water on PACl hydrolysis are additive. Hydrolysis of high-basicity PACl by bicarbonate is slow and hence needs sulfate ions. Large hydrolysis power of sulfate is due to its divalency and tetrahedral structure. Abstract: Application of poly-aluminum chloride (PACl) coagulant is a popular mode of water treatment worldwide because of the high capacity of PACl to neutralize charge. The manufacture and use of PACls with various basicities in different regions around the world suggest that the characteristics of the raw water are important determinants of the efficacy of PACl application. However, attention has not been fully paid to the effects of water quality other than the substances to be removed. In this study, two typical PACls with different basicities were used to investigate why the performance of PACls depends on the characteristics of the raw water. We focused on the concentrations of inorganic ions in the raw water. Use of high-basicity PACl (HB-PACl) with a high content of polymeric-colloidal species (Alb +Alc ) resulted in very slow floc formation and little turbidity removal in raw water with low concentrations of sulfate ions. The performance of the HB-PACl was inferior to that of normal-basicity PACl (NB-PACl), although the charge-neutralization capacity of the HB-PACl was higher. Rates of floc formation were strongly correlated with the rate of aluminum precipitation by hydrolysis reaction, which was identified as an indicator for evaluating the compatibility of raw water with PACl treatment. Among the common ions in natural water, the sulfate ion had the greatest ability to hydrolyze and precipitate PACl because of its divalency and tetrahedral structure. This conclusion followed from experimental results showing similar effects for selenate and chromate ions as for sulfate ions and somewhat smaller effects for thiosulfate ions. Bicarbonate ions and natural organic matter affected PACl hydrolysis-precipitation, but chloride ions, nitrate ions, and cations had little effect on PACl hydrolysis-precipitation. Interestingly, the abilities of sulfate ions to hydrolyze HB-PACl and NB-PACl were very similar, but bicarbonate ions were less effective in hydrolyzing HB-PACl than NB-PACl, and bicarbonate ions contributed little to the hydrolysis-precipitation of HB-PACl in raw water with normal alkalinity. Therefore, sufficient coagulation with HB-PACl therefore usually requires a certain concentration of sulfate ions in water to be treated. The implication is that which anions are most influential to the hydrolysis-precipitation of PACl, and thus to PACl's coagulation ability depends on the constituents of the PACl. Graphical abstract: Image, graphical abstract